Juridical Analysis of Crypto Currency Regulation in Indonesia and Its Implications for Consumer Protection - Lasut, Meiske; Mesra, Romi (Jurnal Mahkamah Hukum, 2024)
The rise of cryptocurrencies has brought both opportunities for innovation and challenges in safeguarding consumer interests. Indonesia has taken proactive steps to regulate this emerging domain by implementing regulations around trading cryptocurrencies as commodities on dedicated exchanges. However, the current regulatory landscape still exhibits certain gaps that need to be addressed to strengthen consumer protection standards. This research conducts a comprehensive juridical analysis of the existing regulations governing cryptocurrencies in Indonesia. It examines the key provisions aimed at safeguarding consumers such as KYC requirements, mandates around secure asset storage, risk disclosures, and minimum capital standards for exchanges. The analysis also highlights regulatory challenges including lack of comprehensive data protection laws, absence of clear liability frameworks and dispute resolution mechanisms, and limited regulatory capacity. The research discusses the implications of the current regulations, both in terms of potential overregulation stifling innovation and the need for more robust measures enhancing consumer protection. It advocates for a balanced approach of developing an enabling yet risk-based regulatory framework through extensive stakeholder consultation. Legal clarity through unified asset classification, delineating regulatory jurisdictions, detailed guidelines covering consumer rights and taxation are emphasized. Overall, the research argues that while Indonesia has taken positive initial steps, a more nuanced and comprehensive regulation elevating consumer protection without inhibiting innovation in this rapidly evolving space is still imperative. Recommendations for policy measures to bridge the existing gaps are provided.